2018
DOI: 10.1007/s00592-017-1099-2
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes and risk of cardiovascular disease up to 25 years after pregnancy: a retrospective cohort study

Abstract: In this population of pregnant women, gestational diabetes was associated with an increased risk of heart disease 25 years after delivery. Women with gestational diabetes may merit closer monitoring for cardiovascular disease prevention after pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 29 publications
3
79
1
3
Order By: Relevance
“…1). Nine studies met our inclusion criteria [6,8,9,[15][16][17][18][19][20] and were included in the analysis, providing data on 5,390,591 women and 101,424 cardiovascular events (8003 in women with GDM and 93,421 in women without GDM). Table 1 summarises the included studies, which were all published between 2013 and 2018.…”
Section: Resultsmentioning
confidence: 99%
“…1). Nine studies met our inclusion criteria [6,8,9,[15][16][17][18][19][20] and were included in the analysis, providing data on 5,390,591 women and 101,424 cardiovascular events (8003 in women with GDM and 93,421 in women without GDM). Table 1 summarises the included studies, which were all published between 2013 and 2018.…”
Section: Resultsmentioning
confidence: 99%
“…These maternal cardiometabolic disorders have been identified as risk factors for longterm cardiovascular disease. [31][32][33][34][35][36][37][38][39]…”
Section: What Do Pregnancy Complications Indicate About Future Risk Omentioning
confidence: 99%
“…38 In 2018, a Canadian retrospective cohort study involving over 1 million women showed an association between gestational diabetes and elevated ischemic heart disease (HR 1.23, 95% CI 1.12-1.36) and MI (HR 2.14, 95% CI 1.15-2.47) as much as 25 years after the index pregnancy. 39…”
Section: Maternal Dysglycemiamentioning
confidence: 99%
“…There now exists a plethora of literature detailing the relationship between pregnancy complications (including hypertensive disorders of pregnancy, gestational diabetes mellitus, intrauterine growth restriction, idiopathic preterm birth, and placental abruption) and an increased risk of future CVD (11)(12)(13)(14)(15)(16)(17)(18)(19). During pregnancy, maternal physiology undergoes complex and substantial changes, resulting in heightened organ function to cope with fetal demand and to maintain pregnancy (20).…”
Section: Introductionmentioning
confidence: 99%